The importance of the “right to the truth” in El-Masri case: Lessons learned from the extraordinary rendition - Stefanovska, Vesna (Torture Journal, 2021)
Introduction: In December 2012 the European Court of Human Rights (the Court or ECtHR) delivered the landmark decision in the case of El-Masri v. F.Y.R Macedonia (‘Macedonia’) ruling that CIA extraordinary rendition program amounts to torture. Macedonia was held responsible for torture and detention of El-Masri; lack of conducting effective interrogation; lack of request for diplomatic assurances from CIA agents and interference with the right to private and family life. Some of the judges referred to the right of the truth as the right of El-Masri to be familiar with the facts why he was held incommunicado and being subject of the CIA extraordinary rendition program. Objective: By using the El-Masri v. Macedonia case, this paper aims to map the necessity for protection of human rights even when national security and war against terrorism are at stake. The right to the truth should be of utmost importance besides proving torture –it is the way for the victim to accomplish moral victory and to gather all facts of the case. Method: The relevant texts were gathered from the HUDOC database, Cambridge University Press, Google Scholar, while interviews were conducted with Margarita Tsatsa Nikolovska – former judge in the European Court of Human Rights and Aleksandar Bozinovski – the journalist who discovered to the public the extraordinary rendition of Khaled El-Masri. Results/Discussion: the ruling in the El-Masri case was the first time when an international court held that the CIA’s extraordinary rendition program amounts to torture. However, the Court did not argue about the culpability of CIA agents nor the explanations how Macedonia can be held accountable for torture committed in a foreign country by foreign agents just because of lack of diplomatic assurances and allowed extraordinary rendition at the Skopje Airport.